2020
DOI: 10.1055/s-0040-1706296
|View full text |Cite
|
Sign up to set email alerts
|

OxymaPure Coupling Reagents: Beyond Solid-Phase Peptide Synthesis

Abstract: OxymaPure [ethyl 2-cyano-2-(hydroxyimino)acetate] is an exceptional reagent with which to suppress racemization and enhance coupling efficiency during amide bond formation. The tremendous popularity of OxymaPure has led to the development of several Oxyma-based reagents. OxymaPure and its derived reagents are widely used in solid- and solution-phase peptide chemistry. This review summarizes the recent developments and applications of OxymaPure and Oxyma-based reagents in peptide chemistry, in particular in sol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 96 publications
0
10
0
Order By: Relevance
“…[34] These methods have demonstrated cost-effectiveness and broad applicability. However, with the impressive number of recent reviews on sustainable amide synthesis progress, [35][36][37][38][39][40][41][42][43][44][45][46][47][48][49] it is clear that this topic is still of great importance, and there is an urgent need for new, environmentally-friendly approaches.…”
Section: Introductionmentioning
confidence: 99%
“…[34] These methods have demonstrated cost-effectiveness and broad applicability. However, with the impressive number of recent reviews on sustainable amide synthesis progress, [35][36][37][38][39][40][41][42][43][44][45][46][47][48][49] it is clear that this topic is still of great importance, and there is an urgent need for new, environmentally-friendly approaches.…”
Section: Introductionmentioning
confidence: 99%
“…One of the mostly used is ethyl oxyma,‡ which was investigated in this study. 16 Finally, carbodiimides being sensitizing molecules, a carbodiimide-free oxyma-based coupling agent, COMU was also tested. 17…”
mentioning
confidence: 99%
“…One of the mostly used is ethyl oxyma, ‡ which was investigated in this study. 16 Finally, carbodiimides being sensitizing molecules, a carbodiimide-free oxymabased coupling agent, COMU was also tested. 17 EDC.HCl, widely used together with DMAP as a base, in a catalytic amount, in solution or in solvent-free conditions, 4,9,10a,11e,f was investigated.…”
mentioning
confidence: 99%
“…More recently, Dunetz et al 25 confirmed prevention of racemization in T3P® mediated amide formation, selecting pyridine as the most suitable base. We explored herein the possibility to apply this reagent to continuous solution-phase synthesis, eliminating the need for other coupling reagents and carbodiimides, which display several disadvantages in terms of toxicity and safety, 26 aiming at developing a fast and green protocol for oligopeptide synthesis.…”
mentioning
confidence: 99%
“…We explored, herein, the possibility of applying this reagent to continuous solution-phase synthesis, eliminating the need for other coupling reagents and carbodiimides, which display several disadvantages in terms of toxicity and safety, 26 to develop a fast and green protocol for oligopeptide synthesis.…”
mentioning
confidence: 99%